Effects of parity order, age at first calving and season of calving on productive performance of Friesian crossbred cattle in Sudan (Journal of Veterinary Medicine and Animal Production, 2021)
This study was carried out to determine the effects of parity orders, season of calving and age at first calving on total milk yield (TMY) and lactation length (LL) in a herd of Friesian crossbred cattle in Sudan. Data obtained from records from 2002 to 2011. The average TMY and LL were 3988.2 ± 36.2 kg and 355.8 ± 2.4 days, respectively. The TMY and LL were significantly (P ≤ 0.01) affected by parity orders. Highest TMY reported at 6th parity and longest lactation was recorded at 4th parity. Moreover, season of calving was significantly (P ≤0.01) affected on TMY and LL. In addition higher average values for TMY and LL were obtained in wet summer. The age at first calving had a significant (P≤ 0.01) effect on TMY, while heifers calved in late age were significantly (P ≤ 0.01) higher in milk yield than heifers calved in medium and early age.
Keywords: Parity order; age; season; productive performance; crossbred cattle